COST MINIMALIZATION ANALYSIS (CMA) PENGGUNAAN OBAT ANTIHIPERTENSI GOLONGAN CALCIUM CHANNEL BLOCKER KOMBINASI ANGIOTENSIN RECEPTOR BLOCKER PADA PASIEN HIPERTENSI DI RSU IMELDA PEKERJA INDONESIA MEDAN - Gultom, Roby; Silvia, Mariani (Universitas Imelda Medan, 2022)
Hypertension is a degenerative diseases that can take long treatments or even a lifetime. Hypertensive treatment costs tend to be as high as medical costs and other administrations in hospitals, so a CMA analysis is needed to getmoreeconomical and effective treatment cost. The study was intended to learn the minimum costs of the use of drugs from the CCB combination of ARB. The study is a descriptive observational study of retrospective nature. Studies show that of 60 patients there are 24 male patients (40%) and 36 female patients (60%). The average age of most patients between 51-60 years, with the most hospitalization is 1-5 days. The most widely used antihypertension medication is candesartan 8 mg combination of amlodipin 10 mg (42%) and candesartan 16 mg combination of amlodipin 10 mg (25%). Studies have concluded that antihypertension drugs that have a minimum costs (CMA) is candesartan 16 mg combination of amlodipin 10 mg at Rp.3.870.065.-. Where the average costs paid by patients daily for antihypertensive drugs are Rp.4.952.-, treatment costs Rp.167.819.-, doctor costs Rp. 69.619.- and room administration Rp.310.476.-. So the total daily costs incurred by hypertensive patients at RSU Imelda Pekerja Indonesia Medan amounts to Rp.552.866.-.